Correlates of High School Freshman Girls' Reported Reasons for Engaging in Sexual Intercourse. (June 2014) - Smith, Matthew Lee; Wilson, Kelly; Menn, Mindy; Pulczinski, Jairus C.
ABSTRACT BACKGROUND Intrapersonal and external factors, including social pressures and the desire for acceptance from peers, influence sexual activity among adolescents. This study examined how personal characteristics, risky behaviors, normative beliefs, household factors, and engagement in extracurricular activities were related to high school freshman girls' reported reasons for having sexual intercourse. METHODS Baseline data were analyzed from 158 girls enrolled in high school‐based abstinence‐only‐until‐marriage education programs during their freshman year. Binary logistic regression was performed to identify factors associated with Pressures and Reasons for Engaging in Sex Scale (PRESS) scores. RESULTS Results indicate that girls with high PRESS scores were significantly more likely to have had sex (OR = 4.29), consumed alcohol within the previous year (OR = 6.13), reported strict household rules (OR = 1.49), and thought more girls their age had sex (OR = 1.67). CONCLUSION School‐ and family‐based interventions should be developed to encourage and strengthen parent‐teen communication within the household and reinforce self‐worth and positive self‐perceptions among adolescent girls.